Employment Listening Skills in The Teaching Of Recitation: Employment Listening Skills in The Teaching Of Recitation (Journal of the College of Education for Women, 2019)
AbstractWe Can Summarize This Research According To the Following PointsA- result1- We conclude a new method to teach the recitation we call it (listeningmethod) which consist of four steps (introduction , listening ,continuity,evaluation )2- This research get many listening skills that educated need it whenlisten to (holy quran) beside to many propositions that help to developit.3- This research briefs some principles that help the teacher when uselistening method.B- conclusion1- The best way to teach and learn the recitation of holy quran is byusing listening skill because the prophet (pease be upon him )learnthe holy quran by it from jebrel (pease be upon him ) and thenteach the muslims .2- Listen to holy quran in (early years in childhood) that help to fix thecorrect utterances in educated” mind and be easy to learn it in thefuture.3- Arabic language is the language of holy quran so that the best wayto learn it by listening to holy quran because its origin of arabiclanguage standards.C- recommendation1- Listening skill should take important place in teaching the holyquran because its important skill which is neglect in the past .2- Should be attention to learn the children the holy quran and learnthem to listen to it .